PENGARUH BUDAYA CHINA DALAM TARI KLASIK GOLEK MENAK GAYA YOGYAKARTA - , LISTYA ROMALARAS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The arrival of the Chinese in Indonesia since the 5th century brought a lot of influence in Indonesia, not only in terms of trade but also in terms of culture. In this regard, Indonesia has a cultural influence of Chinese culture for example in the field of dance. Indonesia is one of the dances are influenced by the Chinese culture Menak Marionette dance from Yogyakarta. Find a Menak dance is one of the main dances performed at the Sultan's Palace to welcome important guests or guests of state from other countries. In these dances, Chinese culture is affected in terms of make up, a variety of dance movements, and costumes.